RISIKO POSTUR KERJA TERHADAP KELUHAN SUBYEKTIF NYERI LEHER PADA PEKERJA INDUSTRI KERAJINAN KULIT - Ekawati Wasis Wijayati (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2020)
Musculoskeletal complaints are generally felt a lot because of the habits done during work. Body posture when working improperly and maintained in a relatively long time can lead to musculoskeletal complaints. Working in a sitting position for a relatively long period of time with a bent and bent body position can be a risk factor for complaints of neck pain or back pain. This study aims to analyze the relationship between long-standing work posture with subjective complaints of neck pain in leather craft industry workers in Selosari. The study design was an observational analytic study with a cross sectional approach. The sampling technique in this study was proportional random sampling with a sample of 42 respondents from the leather craft industry workers in Selosari. The results of statistical analysis with the Chi Square test showed that p=0.006 (p <0.05), which means there is a relationship between the length of maintaining work posture to subjective complaints of neck pain in leather craft industry workers in Selosari. It should be noted that prolonged retention of neck posture which is too bent when working continuously for long periods of time will increase the risk of neck pain complaints. So it is necessary to improve the posture of the body when working, especially the neck or movement or changes in posture, especially the neck if it starts feeling stiff or stiff in the neck.